Melatonin enhances cisplatin‐induced cell death through inhibition of DERL1 in mesenchymal‐like CD44high OSCC cells. (17th October 2021) - Shigeishi, Hideo; Yokoyama, Sho; Murodumi, Hiroshi; Sakuma, Miyuki; Fukada, Shohei; Okuda, Satoshi; Yamakado, Nao; Ono, Shigehiro; Takechi, Masaaki; Ohta, Kouji
Abstract: Background: Melatonin is a hormone that is primarily produced in the pineal gland and is involved in wide range of biological functions. However, the impact of melatonin on chemotherapy‐induced cell death remains to be elucidated in oral squamous cell carcinoma (OSCC) cells. The objective of this study was to clarify the role of melatonin in cisplatin‐induced cytotoxicity in CD44 high OSCC cells. Methods: CD44 high OSCC cells were cultured on fibronectin‐coated hydrogel. A lactate dehydrogenase cytotoxicity assay was performed to evaluate cisplatin‐induced cell death. The effect of melatonin on cisplatin‐induced cell death and Derlin‐1 (DERL1) endoplasmic reticulum membrane protein expression was investigated. Results: CD44 high OSCC cells exhibited mesenchymal‐like features when cultured on fibronectin‐coated hydrogel. Mesenchymal‐like CD44 high OSCC cells demonstrated strong resistance to cisplatin‐induced cell death compared with epithelial‐like CD44 high OSCC cells. DERL1  mRNA and DERL1 protein expression levels were significantly higher in mesenchymal‐like CD44 high cells compared with epithelial‐like CD44 high cells. Cisplatin‐induced cell death was significantly enhanced after DERL1  siRNA knockdown, suggesting that DERL1 is involved in resistance to cisplatin‐induced cell death. Melatonin significantly inhibited DERL1 expression and enhanced cisplatin‐induced cell death in mesenchymal‐like CD44 high cells. miR ‐ 181c ‐ 5p expression was significantly upregulated in the presence of melatonin. Furthermore, melatonin‐inhibited DERL1 expression was significantly recovered by miR ‐ 181c ‐ 5p inhibitor. In addition, melatoninenhanced cisplatin‐induced cell death was attenuated by miR ‐ 181c ‐ 5p inhibitor. These results suggest that melatonin‐induced miR ‐ 181c ‐ 5p enhances cisplatin‐induced cell death through inhibition of DERL1 in mesenchymal‐like CD44 high cells. Conclusions: Melatonin plays a vital role in promoting cisplatin‐induced cytotoxicity in mesenchymal‐like CD44 high OSCC cells.